Reversed-Phase Liquid Chromatographic Separation and Determination of Ni(II), Cu(II), Pd(II), and Ag(I) Using 2-Pyrrolecarboxaldehyde-4-phenylsemicarbazone as a Complexing Reagent. (1st November 2013) - Mallah, Arfana; Solangi, Amber R.; Memon, Najma; Memon, Rabia A.; Khuhawar, Muhammad Y.
Abstract : This paper reports the utilization of 2-pyrrolecarboxaldehyde-4-phenylsemicarbazone (PPS) as a complexing reagent for the simultaneous determination and separation of Ni(II), Cu(II), Pd(II), and Ag(I) by reversed-phase high-performance liquid chromatography with UV detector. A good separation was achieved using Microsorb C18 column (150 × 4.6 mm i.d.) with a mobile phase consisted of methanol : acetonitrile : water : sodium acetate (1 mM) (68 : 6.5 : 25 : 0.5 v/v/v/v) at a flow rate of 1 mL/min. The detection was performed at 280 nm. The linear calibration range was 2–10 μ g/mL for all metal ions. The detection limits (S/N = 3) were 80 pg/mL for Ni(II), 0.8 ng/mL for Cu(II), 0.16 ng/mL for Pd(II), and 0.8 ng/mL for Ag(I). The applicability and the accuracy of the developed method were estimated by the analysis of Ni(II) in hydrogenated oil (ghee) samples and Pd(II) in palladium charcoal.